1970
DOI: 10.3329/bjas.v37i2.9878
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation Of Bangladesh Livestock Research Institute Cattle Breed-1 : Heritability And Genetic Correlation

Abstract: Heritability and genetic correlation of economic traits of Bangladesh Livestock Research Institute (BLRI) Cattle Breed-1 (BCB-1) were estimated with Residual Maximum Likelihood (REML) principle. The BCB-1 is a native cattle breed developed by BLRI through selective breeding among indigenous cattle of Bangladesh. Data asserted from performance record sheets of 500 animals maintained during 1992 to 2005 were analyzed for estimation of genetic parameters. The heritabilities were estimated with single trait animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
2
3
1
Order By: Relevance
“…The magnitude of the estimates obtained in the present study is not far from previous reports of about 0.5-0.6 (Pryce et al, 2000;Dal Zotto et al, 2007;Fu et al, 2017). Deb et al (2008) reported a genetic correlation of 0.4 between CI and MY in a native breed from Bangladesh. Antagonistic genetic correlation between MY and CI was also observed by Haile-Mariam et al (2003) and by Strapáková et al (2016).…”
Section: Calving Interval Production Traits and Lactation Persistencycontrasting
confidence: 66%
“…The magnitude of the estimates obtained in the present study is not far from previous reports of about 0.5-0.6 (Pryce et al, 2000;Dal Zotto et al, 2007;Fu et al, 2017). Deb et al (2008) reported a genetic correlation of 0.4 between CI and MY in a native breed from Bangladesh. Antagonistic genetic correlation between MY and CI was also observed by Haile-Mariam et al (2003) and by Strapáková et al (2016).…”
Section: Calving Interval Production Traits and Lactation Persistencycontrasting
confidence: 66%
“…The genetic (r g = 0.81) and phenotypic correlation (r p = 0.75) estimates between age at first service and age at first calving observed were positive and strong (Table 4) that was as expected from close link between their measurements and were quite similar to finding reported by Deb et al, 2008 in crossbred cattle. The result of this study were also consistent with the earlier studies of Saha, 2001 (r g = 0.55, r p = 0.85) and Haile et al, 2009 (r g = 0.88, r p = 0.73) in Karan Fries and Boran crossbred cattle respectively.…”
Section: Genetic and Phenotypic Correlationsupporting
confidence: 76%
“…Estimation of heritability and genetic correlation of economic traits will help in planning further genetic improvement programme of any breed. Accordingly, heritability of production and reproduction traits such as lactation milk yield, lactation length, peak milk yield, dry period, age at first service, age at first calving, post-partum onset of heat, services per conception and calving interval (Aaron et al, 1987, Deb et al, 2008, Verma et al, 2018. Moreover, genetic parameters of Holstein crossbred cows were evaluated in commercial dairy farms in Bangladesh .…”
Section: Genetic Parameters Estimationmentioning
confidence: 99%